Bhutan : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bhutan. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the 2007 Article IV Consultation on Bhutan explains the macroeconomic setting, economic developments, outlooks, risks, and challenges. Bhutan's economic prospects are bright. Construction of two hydropower projects will help sustain real GDP growth over the medium term. With the exchange rate peg to the Indian rupee, inflation is expected to be in line with price developments in India. Executive Directors commended Bhutan's prudent macroeconomic policies and political stability, which have yielded robust growth, an appreciable improvement in social indicators, and progress toward meeting the Millennium Development Goals.